General-equilibrium implications of international product-market competition for jobs and wages - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 2001)
This paper extends the insight that trade increases international product-market competition to show that in a world with an endogenous natural rate of unemployment, countries can benefit through a decline in the natural rate. When the number of firms in the integrated world market is greater than the number of firms in each economy in autarky, all trading nations in a world of identical factor proportions experience a decline in equilibrium unemployment. When factor proportions differ, equilibrium unemployment must fall in the labor-abundant country but may rise or decline in the capital-abundant country.